System Model for Prediction of Energy Consumption in Cities. (June 2019) - Vytlačil, D
Abstract: The number of inhabitants in cities has been increasing in the past years and this tendency will be in the future even more significant. We need a tool for the prediction of the energy consumption. The paper describes the system model that includes sub models: the energy consumed for housing, inhabitants services, city services and transport. These sub models are interconnected to one system. The solution is based on the system dynamics methodology which is suitable tool for solving problems of economic and technical systems. Special focus is given on the description of the energy consumptions in the residential houses, in the buildings providing city service and on the migration of people from rural area and small cities to big cities. The number of inhabitants influences the energy consumption and the density that is connected to the energy consumption for the transport. The simulation includes the refurbishment of the existing building stock. Main output parameter is the energy consumption in the sub models and in the whole city. The model can help to improve the strategy decision making concerning city development.